The influence of social determinants of health on the quality of life and healing of patients with chronic venous ulcers: An integrative literature review (Research, Society and Development, 2026)
Chronic venous ulcers constitute a significant public health problem, affecting patients’ quality of life and being influenced by social, economic, and cultural factors. Nursing plays an essential role in care, acting in wound management, guidance, and support for patients, considering the Social Determinants of Health. This study aims to analyze the influence of the Social Determinants of Health on the quality of life and the healing process of patients with chronic venous ulcers, as well as the role of nursing in this context. The results indicate that factors such as low income, limited education, difficulties in accessing health services, and fragile social support networks interfere with healing and patients’ quality of life, highlighting the importance of nursing in comprehensive care.